Everyday Magic or Winter Haunting? Kevin Sullivan’s Supernatural Re-Visioning of L. M. Montgomery’s Jane of Lantern Hill - Heidi Lawrence (Canada and Beyond)
L. M. Montgomery’s Jane of Lantern Hill employs the natural magic of “Jane Victoria” Stuart’s environment to convey psychological changes and healing for the main character in what appears to be an immersive fantasy comprised of a Prince Edward Island that provides a magical setting for Jane’s emotional and social development. In contrast Kevin Sullivan’s film adaptation, Lantern Hill, employs the magic of the supernatural to achieve those same psychological impacts on Victoria Jane in something akin to an intrusion fantasy, in which ghosts and haunting dreams propel both Jane and the viewer into an almost-Gothic Prince Edward Island. This article explores the impact of those changes and suggests that the magic of Montgomery’s story, which can be revealed over time through beautiful imagery and language in the novel, must be conveyed quickly through highly visual and auditory means in the film, raising questions about the gaps created between natural and supernatural magic and how those gaps change the meaning or outcome of the story.